2008
DOI: 10.1007/s10750-007-9205-z
|View full text |Cite
|
Sign up to set email alerts
|

Pollen, diatom and plant macrofossil assemblages indicate a low water level phase of Lake Peipsi at the beginning of the Holocene

Abstract: During the Fennoscandian ice recession from the eastern Baltic area, the water level in the Lake Peipsi basin was decreasing and reached a minimum at the end of the Younger Dryas Chronozone. The low lake level episode is represented in the basal deposits by a ca. 0.8 m thick bed of coarse detritus gyttja dated to 9.6-9.1 ka 14 C BP. The gyttja lies at an elevation of 20-21 m a.s.l., i.e. about 9 m below the present lake level (30 m a.s.l.), and is buried under a 1.5-2 m bed of fine to medium-grained sand. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…According to Hang et al [24], at the onset of the Holocene a low-level period occurred during which 'Small Lake Peipsi', with a water level 8 m lower than today, existed. In addition, the presence of lake lime layers in between late glacial clays and gyttja Downloaded by [INASP -Pakistan (PERI)] at 21: beds in several locations of the basin has been associated with an early Holocene lake level low stand [6,25,26]. Therefore, we attribute the up-core transition from low to high sediment particulate OM content to a progressively deepening water body.…”
Section: Temporal Changes Of Sediment Pore-water Dom Characteristicsmentioning
confidence: 92%
“…According to Hang et al [24], at the onset of the Holocene a low-level period occurred during which 'Small Lake Peipsi', with a water level 8 m lower than today, existed. In addition, the presence of lake lime layers in between late glacial clays and gyttja Downloaded by [INASP -Pakistan (PERI)] at 21: beds in several locations of the basin has been associated with an early Holocene lake level low stand [6,25,26]. Therefore, we attribute the up-core transition from low to high sediment particulate OM content to a progressively deepening water body.…”
Section: Temporal Changes Of Sediment Pore-water Dom Characteristicsmentioning
confidence: 92%
“…Firstly, the litho-and chronostratigraphy of the core carry a clear sign of about a thousand-year hiatus during the early Holocene, suggesting that the lake level was low enough at the coring site so that the wind-induced wave stress caused sediment motion and relocation. Hang et al (2008) reported that the basin of Lake Peipsi passed a rapid and tremendous regression at the end of the late-glacial and the low stand continued during the early Holocene, reaching its minimum, i.e. *8 m below current water level, *10.2 cal kyr BP.…”
Section: Stages In the Lake Evolutionmentioning
confidence: 99%
“…Lake Peipsi is a large but relatively shallow temperate lake located in the northern hemisphere. According to Hang et al (2008), the last deglaciation of its basin started *14.4 cal kyr BP; by the onset of the Holocene, *11.5 cal kyr BP, a low-level lake, called Small Lake Peipsi, with the water level 10 m lower than today had formed. The knowledge about the conditions and development of the lake over the next 10,000 yr is scarce and mostly based on a few studies of poorly dated diatom and geochemical records (Davydova, 1985;Davydova & Kimmel, 1991;Punning et al, 2008) with a very low time resolution.…”
Section: Introductionmentioning
confidence: 99%
“…Paleolimnological investigations (including diatom analyses) in Lake Peipsi have been carried out by Heinsalu et al (2007 and Hang et al (2008). However, the knowledge of diatom assemblages in Lake Peipsi is still limited, and very little is known of the relationship between the diatom assemblages and their relationship to sediment composition.…”
Section: Introductionmentioning
confidence: 99%